Dignity in the legal and political philosophy of Ronald Dworkin - Khurshid, Salman; Malik, Lokendra; Rodriguez-Blanco, Veronica (Oxford University Press India, 2018)
Well-known for his contribution to the juristic world, Professor Ronald Dworkin was an outstanding legal philosopher of his generation. This volume celebrates the thoughts of Ronald Dworkin on dignity. The contributors have critically engaged with different perspectives of Dworkin's thoughts on dignity. The aim is to shed light on juridical and moral contemporary conundrums such as the role of dignity in constitutional contexts in India, and the understanding of dignity as either a foundation of human rights or as a supra value that illuminates other values and rights.